Introducing biomimetic shear and ion gradients to microfluidic spinning improves silk fiber strength. (31st May 2017) - Li, David; Jacobsen, Matthew M; Gyune Rim, Nae; Backman, Daniel; Kaplan, David L; Wong, Joyce Y
Abstract: Silkworm silk is an attractive biopolymer for biomedical applications due to its high mechanical strength and biocompatibility; as a result, there is increasing interest in scalable devices to spin silk and recombinant silk so as to improve and customize their properties for diverse biomedical purposes (Vepari and Kaplan 2007 Prog. Polym. Sci. 32 ). While artificial spinning of regenerated silk fibroins adds tunability to properties such as degradation rate and surface functionalization, the resulting fibers do not yet approach the mechanical strength of native silkworm silk. These drawbacks reduce the applicability and attractiveness of artificial silk (Kinahan et al 2011 Biomacromolecules 12 ). Here, we used computational fluid dynamic simulations to incorporate shear in tandem with biomimetic ion gradients by coupling a modular novel glass microfluidic device to our previous co-axial flow device. Fibers spun with this combined apparatus demonstrated a significant increase in mechanical strength compared to fibers spun with the basic apparatus alone, with a three-fold increase in Young's modulus and extensibility and a twelve-fold increase in toughness. These results thus demonstrate the critical importance of ionic milieu and shear stress in spinning strong fibers from solubilized silk fibroin.